Distributed control applications using local area networks: a LAN based power control system at Rhodes University - Sullivan, Anthony John (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2002)
This thesis describes the design and development of both the hardware and software of an embedded, distributed control system using a LAN infrastructure for communication between nodes. The primary application of this system is for power monitoring and control at Rhodes University. Both the hardware and software have been developed to provide a modular and scalable system capable of growing and adapting to meet the changing demands placed on it. The software includes a custom written Internet Protocol stack for use in the embedded environment, with a small code footprint and low processing overheads. There is also Linux-based control software, which includes a web-based device management interface and graphical output. Problems specific to the application are discussed as well as their solutions, with particular attention to the constraints of an embedded system.
Keywords: Embedded computer systems; Local area networks (Computer networks); Linux